Creative Economy and Its Contribution to National GDP: A Study on the Digital Content Sector - Eva Purnamasari; Yusran Zainuddin; Sufnirayanti; Septi Wifasari (Nomico, 2025)
The digital content sector has emerged as one of the most dynamic components of Indonesia's creative economy, reflecting both economic potential and cultural innovation. Despite its rapid expansion, few studies have examined its quantitative impact on national economic indicators. This study aims to analyze the contribution of the digital content sector to Indonesia's Gross Domestic Product (GDP), while also identifying its development dynamics in terms of opportunities, challenges, and strategic policy directions. A mixed-method approach was employed, combining secondary quantitative data from 2019 to 2023 with qualitative insights gathered through interviews with stakeholders in government, industry, and academia. The findings show that the sector's contribution to the creative economy grew from 15.2% to 20.3%, with substantial increases in export value and employment. The results highlight the sector's growing importance in national economic development, driven by youth creativity and digital penetration. However, structural barriers such as limited access to funding, weak intellectual property enforcement, and digital infrastructure inequality persist. This study concludes that unlocking the sector's full potential requires coordinated policy efforts, including digital investment, local content promotion, and inclusive ecosystem support. The digital content industry thus stands as a strategic pillar for Indonesia's innovation-driven and culturally grounded economic future.